Pemenuhan Kebutuhan Pasangan dengan Love Language yang Berbeda pada Mahasiswa - Anastasia Jesslyn Budijono; Tifara Levi; Marissa Gabriele Hadibroto; Jessica Natalie Cheriselyn; Sophie Asha Putri (Universitas Ciputra Surabaya, 2026)
Differing love languages can cause several aspects of needs in a romantic relationship to be unmet. Based on the high prevalence of romantic relationships in university students and the high chance of differing love languages within the relationship, this research aims to find out how couples with differing love languages can meet each others’ needs. This research is carried out using a qualitative method with instrumental study case design to 2 couples each with differing love languages. The analysis technique used in this research is the thematic analysis technique. Results show new findings that the fulfillment of needs in couples with differing love languages is done with communication, understanding, acceptance and most importantly willingness to sacrifice. This must be done by both parties. The limitation present in this study lies in the participants’ early dating age, which prevents the relevancy of data findings for long-term couples.